dining with Russian Old Believers: guesthood, gender roles and rules of ritual purity - rygovskiy, danila (Material religion, 2022)
This paper discusses religious restrictions of the Old Believers, a group within Russian Orthodox Christianity. In particular, I refer to communities of the Chasovenny faction in Siberia. These Old Believers are supposed to eat separately from anyone who does not belong to the group and to use tableware (the so-called “fine bowls”) that are not shared with anyone except community members to avoid defilement. I observe my own field experiences as a guest in these communities, in which the practice of separation is often performed ad hoc. I argue that, despite seeming to establish strict isolation from non-Old Believers, the rule of separate tableware is more important for structuring social relations within the group than for drawing boundary lines between different confessions. I also focus on the gendered aspects of this practice. Maintenance of ritual purity concerns both women and men, but it is represented in their lives differently. The rule requires women to keep profound knowledge of dogmas and local community practices because this is important for supporting other aspects of group religious and social life.